Perinatal Bisphenol A Exposure and Reprogramming of Imprinted Gene Expression in the Adult Mouse Brain - Malloy, Maureen A.; Kochmanski, Joseph J.; Jones, Tamara R.; Colacino, Justin A.; Goodrich, Jaclyn M.; Dolinoy, Dana C.; Svoboda, Laurie K. (Frontiers in Genetics, 2019)
Genomic imprinting, a phenomenon by which genes are expressed in a monoallelic, parent-of-origin-dependent fashion, is critical for normal brain development. Expression of imprinted genes is regulated via epigenetic mechanisms, including DNA methylation (5-methylcytosine, 5mC), and disruptions in imprinting lead to disease. Early-life exposure to the endocrine disrupting chemical bisphenol A (BPA) is associated with abnormalities in brain development and behavior, as well as with disruptions in epigenetic patterning, including 5mC and DNA hydroxymethylation (5-hydroxymethylcytosine, 5hmC). Using an established mouse model of perinatal environmental exposure, the objective of this study was to examine the effects of perinatal BPA exposure on epigenetic regulation of imprinted gene expression in adult mice. Two weeks prior to mating, dams were assigned to control chow or chow containing an environmentally relevant dose (50µg/kg) of BPA. Exposure continued until offspring were weaned at post-natal day 21, and animals were followed until 10 months of age. Expression of three imprinted genes - Pde10a, Ppp1r9a, and Kcnq1, as well as three genes encoding proteins critical for regulation of 5mC and 5hmC – Dnmt1, Tet1, and Tet2, were evaluated in the right cortex and midbrain using qRT-PCR. Perinatal BPA exposure was associated with a significant increase in adult Kcnq1 (p= 0.04) and Dnmt1 (p= 0.02) expression in the right cortex, as well as increased expression of Tet2 in the midbrain (p= 0.03). Expression of Tet2 and Kcnq1 were positively correlated in the midbrain. Analysis of 5mC and 5hmC at the Kcnq1 locus was conducted in parallel samples using standard and oxidative bisulfite conversion followed by pyrosequencing. This analysis revealed enrichment of both 5mC and 5hmC at this locus in both brain regions. No significant changes in 5mC and 5hmC at Kcnq1 were observed with perinatal BPA exposure. Together, these data suggest that perinatal BPA exposure results in altered expression of Kcnq1, Dnmt1, and Tet2 in the adult mouse brain. Further studies with larger sample sizes are necessary to understand the mechanistic basis for these changes, as well as to determine the implications they have for brain development and function.